Melatonin Absence Leads to Long-Term Leptin Resistance and Overweight in Rats - Buonfiglio, Daniella; Parthimos, Rafaela; Dantas, Rosana; Cerqueira Silva, Raysa; Gomes, Guilherme; Andrade-Silva, Jéssica; Ramos-Lobo, Angela; Amaral, Fernanda Gaspar; Matos, Raphael; Sinésio, José; Motta-Teixeira, Lívia Clemente; Donato, José; et al. (Frontiers in Endocrinology, 2018)
Melatonin (Mel), a molecule that conveys photoperiodic information to the organisms, is also involved in the regulation of energy homeostasis. Mechanisms of action of Mel in the energy balance remain unclear; herein we investigated how Mel regulates energy intake and expenditure to promote a proper energy balance. Male Wistar rats were assigned to Control, Control+Mel, Pinealectomized (PINX) and PINX+Mel groups. To restore a 24-hour rhythm, Mel (1mg/kg) was added to the drinking water exclusively during the dark phase for 13 weeks. After this treatment period, rats were subjected to a 24-hour fasting test, an acute leptin responsiveness test and cold challenge. Mel treatment reduced food intake, body weight and adiposity. When challenged to 24-hour fasting, Mel-treated rats also showed reduced hyperphagia when the food was replaced. Remarkably, PINX-rats exhibited leptin resistance; this was likely related to the capacity of leptin to affect body weight, food intake and hypothalamic STAT3 phosphorylation, all of which were reduced. Mel treatment restored leptin sensitivity in PINX-rats. An increased hypothalamic expression of agouti-related peptide (Agrp), neuropeptide Y (Npy) and Orexin was observed in the PINX group while Mel treatment reduced the expression of Agrp and Orexin. In addition, PINX-rats presented lower UCP1 protein levels in the BAT and required higher tail vasoconstriction to get a proper thermogenic response to cold challenge. Our findings reveal a previously unrecognized interaction of Mel and leptin in the hypothalamus to regulate the energy balance. These findings may help to explain the high incidence of metabolic diseases in individuals exposed to light at night.